DYNAMIC TRAFFIC RE-ROUTING AS A METHOD OF REDUCING THE CONGESTION LEVEL OF ROAD NETWORK ELEMENTS - Aleksandr, Novikov; Vladimir, Zyryanov; Anastasiya, Feofilova (Journal of Applied Engineering Science, 2018)
The article presents the main points of the dynamic traffic re-routing on the base of the Intelligent Transport System (ITS). Re-routing problem on the road network has been object many research and different tools have been proposed to increase the traffic management systems effectiveness. In this paper we study some of the issues associated with the simulation of various dynamic route guidance algorithms, focusing on the estimation of their effective using set of traffic parameters. It was founding the main condition for using the method of dynamic traffic rerouting is not only the fact or high probability of occurrence of a traffic incident, but the detection of a process of deterioration of traffic conditions, leading to the formation of congestion in the lack or ineffectiveness of active control. Our research aimed at determination the congestion threshold, alternative routes, average number of re-routing vehicles and duration of re-routing. Also in this paper is presented and explained the most important part of the dynamic traffic re-routing problem - the conceptual diagram of the main stages of the dynamic traffic re-routing.